Legacy and Emerging Pollutants and Their Effects through the Lens of Environmental Management - Samaras, Petros; Kasiteropoulou, Dorothea S.; Emmanouil, Christina (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
In pursuing global economic development, the necessity of efficient environmental protection to achieve sustainable development is sometimes forgotten. One aspect of this problem includes expansive industrialization and urbanization, which introduce both legacy and emerging pollutants into our environment. These risks have become a topic of major concern, as chemical or biological agents are widely and increasingly used in numerous activities, resulting in their continued release and recirculation into the environment through different routes. Pollutants may exert distinct and profound effects on ecosystems. In terrestrial systems, they may disrupt soil microbiota and impair the soil’s fertility and plant growth, or they may bioaccumulate within higher animals, affecting reproductive health and longevity. In aquatic ecosystems, they may interfere with the reproduction and nutrition of many species, impacting food webs and biodiversity. In this context, the present Reprint explores the landscape of classic (legacy) and emerging pollutants, focusing on novel monitoring methods, as well as on less well-studied impacts of pollution on organisms and ecosystems. Understanding pollutant behavior across environmental compartments, unraveling their detailed effects on ecosystems, and mitigating their impacts on life will be critical in safeguarding our planet’s future.